The rare side effect of DPwT vaccination: Status epilepticus and encephalopathy - Dr. Dipesh Kaushik; Dr. Ankur Dharmani; Dr. Arvind Sood (Pediatric Review: International Journal of Pediatric Research, 2021)
Serious adverse effects have been reported with the DTwP vaccine but are rare. The frequency of these side effects/1000 doses is 0.2-4.4 for fever more than 40.5 C, 4-8.8 for persistent crying, 0.06-0.8 for hypotonic hyporesponsive episodes, 0.16-0.39 for seizures, 0.007 for encephalopathy. A 2-month-old male infant presented to the emergency pediatrics outpatient of our hospital with complaints of fever and abnormal body movements. Fever subsided after taking paracetamol. Then after 5 hours of the onset of fever patient had episodes of abnormal body movements in the form of jerky movements of bilateral upper and lower limbs. They started on methylprednisolone therapy. The seizure becomes passive after 24 hours. Antiepileptics were tapered off over 48 hours. In conclusion, although the acellular pertussis vaccine is safer than the cellular vaccine, it may rarely lead to adverse effects such as seizures.